Vulnerabilities in digital platform-based work in the field of online transportation - Noorikhsan, Faisal Fadilla; Khoerunisa, Nisa; Nurohman, Taufik; Muchariman, Randi; Hamzah, Risna Amalia (Universitas Islam Malang, 2024)
This study investigates the vulnerabilities and the illusion of well-being in platform-based digital work, focusing on drivers from Grab, Maxim, and Gojek in Tasikmalaya City. The urgency of this research arises from the rapid growth of the platform economy in Indonesia, which often overlooks the welfare of its workers. The primary objective of this study is to identify the factors affecting the vulnerability of drivers in achieving true well-being, as well as to analyze how the illusion of well-being is produced and maintained in platform-based work. The method used is a qualitative approach with a case study to illustrate the digital work vulnerabilities of Gojek drivers. Data were collected through document studies and Focus Group Discussions (FGDs) with representatives of drivers in Tasikmalaya City, and then analyzed through data reduction, data presentation, verification, and conclusion drawing. The findings indicate that online drivers in Tasikmalaya City face various vulnerabilities, such as a lack of social security and uncertain income. Therefore, collaboration between companies, the government, and driver partners is needed to improve their well-being. Proposed solutions include tariff transparency, the development of a social security scheme, and improved communication between the parties involved. In the future, it is hoped that a fairer and more sustainable partnership for the well-being of online drivers in Indonesia can be established.